Še enkrat o integriranem/celostnem pouku z zornega kota književne didaktike - Kordigel Aberšek, Metka (Jezik in slovstvo, 1998)
Against the background of current heated discussions about the appropriateness of the integrated model of education in the first four years of primary school, the author reviews the model in terms of objectives of both science and literary courses. The fictional worlds of fairy tales and fantastic literature have effect within the subjective cognitive scheme. Literary texts of this kind involve a type of response to reality comparable to that of animistic cognition tipical of children at the pre-operative (=pre-school) stage of their cognitive development. Cognitive psychology (which is claimed to be the basis of the integrated model!) calls for lower grades curricula that would go beyond the level of concrete intellectual operations and stimulate development of formal logical intellectual operations. This objective rules out the use of literary texts whose fictional world is regulated by principles typical of the earlier, in most children already surpassed, stage of intuitive intelligence. From the point of view of literary education, the integrated model is disastrous. In it, literary education objectives would supposedly be achieved as side-effect of pursuing other objectives. The use of a literary text in "preparing pupils for a thematic complex" or as a didactic instrument "to learn a natural/technical structure" ignores the fact that reading a text involves two very different reading situations. Even more, the place and role assigned to the literary text in the integrated model imply that all texts are primarily meant to help the child in learning about the world and the principles governing it. As the integrated model does not develop the child's ability to distinguish reading situations and reading objectives, the child cannot chose a reading strategy appropriate for a given text. In other words, the child does know when he should extract from the text a necessary amount of data in a minimum possible time to reach the objective of his reading, and when the reading speed does not matter, because reading should be a source of literary aesthetic experience, and, therefore, should not be as short as possible. Not distinguishing between the pragmatic and literary perceptive situations, the child enters into both of them with misplaced expectations. He evaluates literature in terms of its informative content and exactness. This is of course completely inadequate. By definition, literature is more than is cognitive component only. With the integrated model not developing the child's ability to recognize the reception situation, the child will not learn to know when the meaning of a text can be grasped simply by putting together the data in it, and when a text has a lot of'empty space' to be filled in by the reader's own imagination
Keywords: integrirani pouk; didactic method; didaktika; književnost; literature; osnovne šole